Idiopatické aneuryzma arterie pulmonalis - Holm, F; Palecek, T; Linhart, A; Reznícek, V; Aschermann, M (Vnitrni lekarstvi, 2003)
Aneurysm of pulmonary artery (PAA) is relatively rare clinical finding and appears mostly in association with significant cardiovascular or pulmonary abnormalities and is frequently caused by pulmonary hypertension. Its diagnosis is not difficult. However, guidelines for the treatment were not yet established. Patients with PAA are at risk for sudden death by a rupture of aneurysm. Therefore, surgical correction (graft replacement) is the method of choice. Nevertheless, it seems that certain group of patients with asymptomatic idiopathic aneurysm of pulmonary artery without presence of any serious cardiovascular or pulmonary abnormality can profit from conservative approach. We refer a 62-years old man with idiopathic PAA, in whom we did not indicate surgical correction. However, the long-term follow-up is necessary.
Keywords: Aneurysm; aneurysma; lidé středního věku; lidé; Pulmonary Artery; mužské pohlaví; Male; Middle Aged; arteria pulmonalis; Humans